IMPLEMENTASI ALGORITMA GENETIKA DENGAN TEKNIK SELEKSI TOURNAMENT UNTUK PENYUSUNAN JADWAL KULIAH - Faisal Murtadho; Andi Farmadi; Dodon Turianto Nugrahadi; Irwan Budiman; Dwi Kartini (Fakultas MIPA Universitas Lambung Mangkurat, 2021)
Genetic Algorithms can help human work, one of which is compiling course schedules. Preparation of course schedules, if done manually, will take a long time because you have to make a schedule where there are no schedule conflicts between one course and another. Therefore, this study will implement a Genetic Algorithm for the preparation of course schedules, so that it will speed up the preparation of course schedules compared to manual scheduling. In this study, the Genetic Algorithm with Tournament Selection was carried out with the input of control parameters, namely Population Size = 10, Crossover Rate (CR) = 0.75, and Mutation Rate (MR) = 0.01. In this study, the Genetic Algorithm has succeeded in obtaining the desired solution, namely scheduling courses where there are no schedule conflicts between one course and another. This search process took 88 generations to find the best solution.